Community health workers' mobility in China: Evidence from 2008 to 2017 - Zou, Qi; He, Xiaoqun; Zhang, Liang (Frontiers in Public Health, 2022)
Background: Community health workers (CHWs) are essential to improve the responsiveness of the national health system and capacity of community health services. However, the world is now generally facing CHW shortage. Since the implementation of the new programme for health system reform in 2009, China has adopted unprecedented policy to attract and retain CHWs in an attempt to fairly increase the quantity and quality of CHWs. The policy effects need to be further determined. The purpose of this study is to illustrate the temporal and spatial dynamics of CHWs’ mobility in China from 2008 to 2017. Methods: This study used a multi-stage stratified sampling method to collect a total of 14,094 CHWs’ mobility records from 24 counties and 12 districts in six provinces in China for analysis. The data cover the period from 2008 to 2017. Descriptive statistics, visualization and chi-square test are adopted to analyse the dynamic change characteristics of the number of CHWs from 2008 to 2017. Results: This study found that China’s CHWs were in a state of net inflows from 2008 to 2017. The number of net inflows continued to increase from 2008 to 2011 and had a slight downward trend after that. Turnover of CHWs are more in rural areas, males, physicians, management and support staff, intermediate and senior titles, ≥30 years old group and contractual temporary employees. By contrast, the attraction and retention of CHWs are remarkable among nurses, pharmacists, imaging and laboratory technicians, junior title, junior college degree and above and <30 years old group. Conclusions: China has made great achievements with the policy targeting the attraction and retention of CHWs since the implementation of the new programme for health system reform in 2009. However, the stability of CHWs’ attraction and retention policies in China needs to improve, China must pay attention to the fair allocation of urban and rural areas, dynamically adjust the recruitment structure of health technicians, improve the mechanism for attracting and retaining technicians with higher titles and guarantee the benefits of temporary employees.